TINDAKAN TUTUR KOMISSIF JO MARCH DALAM FILM LITTLE WOMEN - Dinar Afriyani (STKIP Subang, 2026)
This research analyzes commissive speech acts used by Jo March in the film Little Women (2019). The purpose of this research is to describe the types and functions of commissive speech acts found in Jo March's dialogues. This study employs a descriptive qualitative method with a pragmatic approach, drawing on speech act theory proposed by Austin (1962), Searle (1969, 1979), and Yule (1996, 2010), and supported by contextual analysis. The data were taken from Jo March's dialogues in Little Women (2019), and five selected dialogues were used as the main data for analysis. The findings show that Jo March uses commissive speech acts to express intention, willingness, refusal, promise, and commitment. These utterances not only indicate future actions, but also represent Jo's independence, responsibility, affection, and resistance to social expectations. Therefore, commissive speech acts in the film function as an important linguistic device for revealing character, personal values, and emotional relationships.